Comparative Analysis of Multimedia Tools for Enhancing English Grammar Instruction Among Adult Learners in Northeastern Nigeria - Mohammed Sani Ya'u (CV. Media Inti Teknologi, 2025)
This study investigates the effectiveness of multimedia tools such as mobile apps, online platforms, interactive textbooks, and video tutorials in enhancing English grammar instruction for adult learners in Nigeria, an area of growing significance given the rapid adoption of educational technologies worldwide. English plays a vital role in Nigeria's academic and professional landscapes; however, adult learners often face significant challenges in mastering English grammar due to limited exposure, inadequate foundational knowledge, and competing responsibilities. The approaches of this study adapt the mixed-methods framework, combining quantitative surveys with qualitative interviews and observations from classroom settings. A total purposive sample size of 200 adult learners was selected; 30 of these provided rich qualitative data. The study examines learners' perceptions of usability, accessibility, and engagement with multimedia tools, alongside their impact on motivation, interaction, and learning outcomes in grammar acquisition. The results show that mobile apps and online platforms are seen as the most effective tools because of their interactive features, like gamified quizzes and instant feedback. These features make learning more engaging and motivating. Additionally, these tools are easy to access and flexible, allowing learners to study at their own pace and fit lessons into their busy schedules. However, challenges such as content overload and technical difficulties were noted. This study concludes by recommending a blended learning approach to integrate multimedia tools with traditional instruction, which provides practical insights for educators and policymakers aiming to improve adult grammar education in resource-constrained settings.